Safety performance of school buses in the State of Qatar - Mohamed Kharbeche (6579296) (2015)
School buses and minibuses are one of the major modes of traveling for students in the state of Qatar. Many studies pointed to the fact that school buses travelling are safer for students than walking or car riding (Bolte, et al., 2000; Hinch, et al., 2002). For that reason, safety measures and performance of school buses in the State of Qatar should be studied and evaluated carefully and wisely. The project aims were done through merged qualitative and quantitative methods. Initially a safety checklist was constructed for school buses and a comprehensive schools map to evaluate of the current safety measures in school buses and to understand the conditions around the surrounding areas like the location of the bus stops and the availability of signage. Then, the second step focuses on conducting a survey for school bus drivers, school bus guides, students, and parents. Finally, the third steps compares between the school bus safety strategies followed in the State of Qatar and the strategies followed in other high income countries. The results of the field visits revealed many very important statistics for all surveys on the safety of school bus and the surrounding areas as well as the behavior of students and drivers. The results revealed that most of the parents are not happy with the safety while loading and unloading and with the safety procedures. In addition, 43% of school bus users didn’t attend any training or workshops about the safety procedures in school bus. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.46